Leadership for Sustainable and Educational Advancement Advancing Great Leaders and Leadership - Crawford, Joseph (Business, Management and Economics, 2023)
Contemporary leadership scholars have been challenged by the need to develop well-educated citizens capable of tackling climate change and social and environmental sustainability. Across the levels of education, leadership has been applied largely to strategic and governance contexts. That is, dominant models of leadership comprise position-based leadership (e.g., principal leadership) and strategic leadership (e.g., school leadership and distributed leadership). There is an opportunity to better understand how educational leaders emerge, the styles and approaches best suited to influencing in educational settings, and the contextual leadership factors that educational leaders ought to be aware of. This book unpacks these practical issues from a conceptual lens. Likewise, domains of sustainable leadership are also underdeveloped, with a need to better enumerate the ways in which individuals assume leadership roles, sense-make, and co-construct solutions to social and environmental sustainability issues. The focus of this book is on enabling space for scholars to apply leadership theory and theorize alternatives to 21st-century sustainability matters.